Leverage decisions and Financial Performance: Does the CFO Gender Metter? Keputusan Leverage dan Kinerja Keuangan: Apakah Gender CFO Berpengaruh? - Harjan, Sinan (Indonesian Journal of Law and Economics Review, 2024)
This study seeks to determine whether chief financial officer (CFO gender) have financial/ leverage decisions leading to influence the firms’ financial performance (FFP). Therefore, this research aims to explain the leverage decisions mediate the association between the CFO gender and FFP. So, this research built three models: firstly, to test the relationship between the CFO gender and leverage decisions while, the second model the effect of leverage on FFP, and the third model tests the mediation impact of leverage on the association between CFO gender and FFP. These models are built based on the data collected from the listed Chinese firms for the period 2011-2019. In this study, STATA version 13.0 is adopted as the analysis technique which is cover following steps. Descriptive statistics, pairwise correlation test, multi-collinearity test and ordinary Least Squares test. The main finding of the study there is negative and insignificant relationship between CFO gender and FFP while, the leverage decisions mediate that association positively and significantly. The findings of this research add to the existing literature by employing data from China and representative the impact of CFO in decreasing the leverage and that decision influence the corporate performance. Highlights: Examine CFO gender's impact on leverage and financial performance. Analyzed Chinese firms (2011-2019) using STATA; tested mediation models. CFO gender indirectly affects performance; leverage mediates positively, significantly. Keywords: Chief Financial officer, Leverage decisions, Firms Financial Performance